The total synthesis of (−)-strempeliopine via palladium-catalyzed decarboxylative asymmetric allylic alkylation. Issue 9 (7th January 2022) - An, Yi; Wu, Mengjuan; Li, Weijian; Li, Yaling; Wang, Zhenzhen; Xue, Yansong; Tang, Pei; Chen, Fener
Abstract : Total synthesis of (−)-strempeliopine has been achieved via Pd-DAAA and a diastereoselective Bischler–Napieralski/lactamization/iminium reduction sequence. Abstract : In the work reported herein, the concise and enantioselective total synthesis of the Schizozygine alkaloid (−)-strempeliopine was developed. This synthetic strategy featured the palladium-catalyzed decarboxylative asymmetric allylic alkylation of N -benzoyl lactam to set up the absolute configuration at the C20 position, a highly diastereoselective one-pot Bischler–Napieralski/lactamization and iminium reduction sequence for the construction of the pentacyclic core structure, and the late-stage dearomative addition of indole, leading to the otherwise difficult-to-achieve hexacyclic indoline framework with complete control of four neighbouring stereocenters.